Neurological manifestations of Vitamin D defi ciency among medical students - Ahmed Hassan Mitwalli; Durdana Hammad; Rehab B Albakr; Abduallatef Alrashoudi; Abeer Aljomaiah; Sanaa Tulbah; Rawabi Albogomi; Mohammed Mitwalli; Hussam Mitwalli (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
Background and Objective: Vitamin D status and neurological manifestation of Vitamin D defi ciency in medical students is seldom investigated. Design and settings: Cross sectional Survey conducted at King Khalid University Hospital Riyadh Saudi Arabia. Methods: 650 medical students fi lled questionnaire. Serum 25- hydroxyl vitamin D 25(OH) D levels were measured for Vitamin D status, PTH and Calcium were also estimated. Vitamin D defi ciency is defi ned as 25(OH) D < 20 ng/ml (50 nmol/liter), insuffi ciency ;21-29 ng/ml (52. 5- 72. 5 nmol/liter). 25(OH) D levels was assayed in serum by electro-chemi-luminescence immunoassay) ECLIA (by Cobas machine.